AN ANALYSIS OF DEIXIS IN ENGLISH TEXTBOOKS DIALOGUE FOR CLASS VII - Jauhar Helmie; Vina Nurviyani; Neng Asti Nurul Awaliyah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
ABSTRACTThis research paper explores the use of deixis in the English language, specifically focusing on the analysis of deixis found in English Textbooks Dialogue for Class VII students in Indonesia. The study is motivated by the need to understand the historical context of deixis and its practical implications for future linguistic research. The researcher employed a qualitative method to analyze dialogues from chapters 1 to 3 of the textbook "English for Nusantara," published in 2022 under the independent curriculum. The analysis was conducted over one semester, allowing for a comprehensive examination of the types of deixis present in the dialogues. The research methodology included identifying relevant dialogues, classifying the data according to the research problems, and tabulating the types of deixis. The findings revealed various forms of deixis utilized in the textbook, contributing to a deeper understanding of how language functions in social interactions. The study highlights the importance of deixis in facilitating clear communication and expresses gratitude to those who supported the research process. Ultimately, this work aims to inspire further investigations in the field of linguistics and provide valuable insights for educators and researchers alike.Keywords: Deixis, Pragmatic, Textbook, Dialogue, English Language